Influence of testing conditions on thermal distribution and resulting load-bearing capacity of bonded anchors under fire. (1st August 2019) - Al-Mansouri, Omar; Mege, Romain; Pinoteau, Nicolas; Guillet, Thierry; Rémond, Sébastien
Highlights: Pull-out fire tests on bonded anchors for ISO 843-1 fire. Bond strength vs. time curve using resistance integration method based on fire tests. Thermal investigation parameter of pull-out fire tests in the current guidelines. Analysis of the predicted bond resistance for each parameter. Abstract: This paper aims to experimentally apply the existing method for evaluating the pull-out capacity of mechanical anchors under fire, to bonded anchors. Due to the absence of sufficient guidelines for evaluating bonded anchors directly exposed to fire, this experimental work studies the influence of the existing evaluation method on the prediction of the bond resistance and failure time. Different testing conditions and possible configurations for anchors in buildings are explored. The studied influencing parameters are: presence of fixtures, insulation of fixtures, thickness of the concrete bearing element, diameter of the anchor, concrete/steel temperature. The influence of each parameter on the predicted bond resistance and failure time, determined with a design method based on resistance integration is studied. Results show that parameters such as concrete element thickness and attaching metallic fixtures on anchors have a negligible influence on the predicted load-bearing capacity and failure time. However, adopting concrete temperature instead of anchor steel temperature in the resistance integration method, and putting insulation around fixtures may lead to a false estimation of the load-bearing capacity and failure time.